Investigation on anticorrosion performance of polyaniline‐mesoporous MCM‐41 composites in new water‐based epoxy coating. Issue 10 (17th February 2014) - Wang, N.; Wu, Y. H.; Cheng, K. Q.; Zhang, J.
<x xml:space="preserve">Abstract</x> Mesoporous MCM‐41(M(with template)) whose pore channels were filled with cationic surfactant n‐hexadecyltrimethyl‐ammonium bromide (CTAB) and a (hydrophobic) poly(propylene glycol) nucleus terminated by two primary hydroxyl groups (Pluronic F‐127, molecular weight = 11500) inside the pore channels and on the outer surface of the particle, MCM‐41 (M(without template)) whose mixture template inside the pore channels and on the outer surface of the particle were calcinated, were used as new fillers for waterborne epoxy. The corrosion studies were carried out on steel plates coated with formulations containing polyaniline prepared with M(with template) and M(without template). Correspondingly, corrosion performance of the coatings was studied by electrochemical impedance spectroscopy (EIS) in 3.5% NaCl aqueous solution and salt spray test. Coatings prepared from polyaniline (PANI)/M(without template) particles synthesized by in situ polymerization were found to exhibit excellent corrosion resistance much superior to PANI/M(with template) in aggressive environments due to the different interfacial structures between the fillers and the matrix.